Pengaruh Rasio Liquidity, Earnings dan Capital terhadap Laba Bersih pada PT. Bank BTPN Syariah Tbk Periode 2016-2023 - Hafiddudin, Muhamad; Wazin, Wazin; Noeralamsyah, Zenno (Studia Economica : Jurnal Ekonomi Islam, 2024)
This research aims to see the influence of FDR, NPF, ROA and CAR on the net profit of PT Bank BTPN Syariah Tbk for the 2016-2023 period. This research uses a descriptive type of quantitative research. Data was obtained via the official website www.btpnsyariah.com in the form of quarterly financial reports which have been transformed into LN (Natural Logarithm) form and then processed via SPSS version 20 media. The data analysis techniques use multiple linear regression test. The results of this research indicate that partially, PT Bank BTPN Syariah Tbk's net profit cannot be influenced by changes in financial ratios such as FDR, NPF, or ROA. However, a high CAR value affects net profit. Meanwhile, simultaneously, the liquidity, earnings and capital ratios together influence net profit.